Rural People and Communities in the 21st century : Resilience and Transformation - Brown, David L., 1940- (David Louis), author 417413; Schafft, Kai A., 1964-, author 617588 (Cambridge, UK ; Malden, MA : Polity Press, 2011)
Rural people and communities continue to play important social, economic and environmental roles at a time in which societies are rapidly urbanizing, and the identities of local places are increasingly subsumed by flows of people, information and economic activity across global spaces